BIOMIMETIC RESTORATIVE DENTISTRY: INTEGRATED LABORATORY AND CLINICAL ASSESSMENT OF STRENGTH, MARGINAL ADAPTATION, PULP VITALITY AND RESTORATION SURVIVAL (Modern American Journal of Medical and Health Sciences, 2025)
Objective. To provide a holistic evaluation of biomimetic restorative approaches versus conventional methods in terms of mechanical strength, marginal seal, maintenance of pulp vitality, and 12‑month clinical survival.